Model Komunikasi Politik Populis: Sebab, Bentuk, dan Efeknya - Aditya Putra (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2018)
Populism is one of the most knowned and at the same time most debatable concept. Various acticles and paper has been written regarding the definition of populism, along with its constituting elements. Yet, until now there is still no common consensus between social scholars regarding how populism should be define. One way to understand populism is by seeing it as a political communication with certain key elements. The identification of populis communication along with its key elements will path way for an easier and better understanding of populism to be applied in further field research.